Putative effects of Helicobacter pylori in levels of trace elements selenium and magnesium and Interleukine-10 in infected children in Tikrit city - Bayader Jalal Abed Al-Hamed Al- Nuaimi (Tikrit Journal of Pure Science, 2023)
The study was conducted in the city of Tikrit during the period from September 2021 to September 2022. A total of 228 samples were collected from children attending Salah El-Din General Hospital. The samples were divided into two groups: children and the control group. Routine tests are used initially to confirm Helicobacter pylori infection. Including blood and stool tests. The measurement of selenium and magnesium was performed using the atomic absorption technique. Interleukin-10 was also detected, and the results of the study showed a significant decrease in selenium (73.8500 ± 3.88350 and magnesium (.7700 ± .24730), and IL-10 recorded a high level among the patients who were examined (8.18391 (134,3500 ±). At any level Likelihood (0.05) In conclusion, some trace elements as well as some immunological parameters should be monitored regularly and a patient with H. pylori should receive an adequate intake of food.